Manajemen Integrasi Pembelajaran Bahasa Arab di Madrasah Berbasis Pondok Pesantren - Makruf, Imam (IAIN Ponorogo, 2016)
Â Learning Arabic in madrasah nowadays is still yet to show optimal results. Madrasah which based on pesantren in Indonesia is very much. But it is not many that can produce graduates who speak Arabic well. Madrasah Aliyah Al-Mukmin in Sukoharjo is one of madrasah based on pesantren that has an integrative model of learning Arabic and shown to produce graduates who can speak Arabic well. This study focus to analyze the integration management model of learning Arabic. This studies was found that all subjects of religion and Arabic was developed in Arabic, from teaching materials, learning methods, and evaluation process. Arabic language is also used daily in the boarding which is supported by Arabic practical activities. The model is proven to improve all Arabic skills. Thus, this model worthy of adoption at the madrasah based on pesantren for learning Arabic.Â ØªØ¹ÙÙÙ Ø§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ© ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙØ¢Ù ÙÙ Ø§ ÙÙØ¬Ø¹ ÙØ¬Ø§ØØ§ ØªØ§Ù Ø§. Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙÙ Ø¤Ø³Ø³Ø© Ø¹ÙÙ Ø§ÙÙ Ø¹Ø§ÙØ¯ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙØ«ÙØ±Ø©, ÙÙÙÙ ÙÙÙÙØ© Ù ÙÙØ§ Ø§ÙØ°Ù ÙØ§Ø¬Ø ÙØªØØµÙÙ Ø§ÙØ®Ø±ÙØ¬ÙÙ Ø§ÙÙ Ø§ÙØ±ÙÙ ÙÙ ØªÙÙÙ Ø§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ©. Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ¹Ø§ÙÙØ© Ø§ÙÙ Ø¤Ù Ù Ø¨Ø³ÙÙØ§ÙØ±Ø¬ÙØ§ Ù Ù Ø§ØØ¯Ù Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØªÙ ØªØ³ØªØ®Ø¯Ù Ø¥Ø¯Ø§Ø±Ø© Ø§ÙØªØ¹ÙÙÙ Ø§ÙØªÙØ§Ù ÙÙ Ù ÙØ³ØªØ·ÙØ¹ Ø§ÙØ®Ø±ÙØ¬ÙÙ Ù ÙÙØ§ Ø§Ù ÙØªÙÙÙ ÙØ§ Ø¨Ø§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ© ØªÙÙÙ Ø§ Ø¬ÙØ¯Ø§. ÙÙØ±ÙØ¯ ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙØªØÙÙÙ Ø§ÙØ¥Ø¯Ø§Ø±Ø© Ø§ÙØªÙØ§Ù ÙÙØ© ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ©. ÙÙ Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙØ¹Ø±Ù Ø§Ù Ø§ÙØªØ¹ÙÙÙ ÙÙ Ø¬Ù ÙØ¹ Ø§ÙÙ ÙØ§Ø¯ Ø§ÙØ¯Ø±Ø§Ø³ÙØ© Ø§ÙØ¯ÙÙÙØ© ÙØ§ÙÙØºÙÙØ© ÙÙØ§Ù Ø¨Ø§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ© Ø³ÙØ§Ø¡ ÙØ§Ù ÙÙ ÙØªØ§Ø¨Ø© Ø§ÙÙ ÙØ§Ø¯ Ø§ÙØ¯Ø±Ø§Ø³ÙØ© Ù Ø¹Ù ÙÙØ© Ø§ÙØªØ¹ÙÙÙ Ù Ø§ÙØªÙÙÙ . ÙØªÙÙÙ Ø§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ© ÙØºØ© Ø§ÙÙÙÙ ÙØ© ÙÙ Ø§ÙÙ Ø¹ÙØ¯ Ø§ÙÙ Ø¯Ø±Ø³Ù Ù ÙÙ Ù ØªÙÙØ¹ Ø§ÙØ¹Ù ÙÙØ© Ø§ÙÙØºÙÙØ© ÙÙÙ. ÙÙØ³ØªØ·ÙØ¹ ÙØ°Ù Ø§ÙØ¥Ø¯Ø§Ø±Ø© Ø§ÙØªØ¹ÙÙÙ ÙØ© ÙØªØ±ØªÙÙ Ù ÙØ§Ø±Ø§Øª Ø§ÙÙØºÙÙØ© Ù Ù Ø§ÙØªÙØ§Ù ÙØ°. ÙÙØ°ÙÙ Ù Ù Ø§ÙÙ Ù ÙÙ Ø§Ù ØªØ³ØªØ¹Ù Ù ÙØ°Ù Ø§ÙØ¥Ø¯Ø§Ø±Ø© ÙØªØ¹ÙÙÙ Ø§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ© ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ£Ø®Ø±Ù Ø§ÙÙ Ø¤Ø³Ø³Ø© Ø¹ÙÙ Ø§ÙÙ Ø¹Ø§ÙØ¯ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ©.